2014
DOI: 10.1080/00918369.2014.983386
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Religiosity Level and Attitudes Toward Lesbians and Gay Men Among Turkish University Students

Abstract: This study examined the relationships between religiosity levels and attitudes toward lesbians and gay men among freshmen university students in Turkey. The Attitudes Towards Lesbians and Gay Men Scale-Short Form and the Religiosity Scale were administered to 91 male (M = 19.95, SD = 1.48 years) and 171 female (M = 19.23, SD = 1.28 years) students. The findings showed that male freshmen (M = 19.32, SD = 4.97) had more negative attitudes toward gay men than toward lesbians (M = 17.84, SD = 5.25), p = .000. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
3
10
1
8
Order By: Relevance
“…In this study, we found that factors which affect homophobia were being male, religion, not having a family member or acquaintance belonging to a sexual minority group, and low self-esteem. This is consistent with the results of prior studies, which showed that males exhibit higher and more intense rates of homophobia than females [20,26,27]. As Korean society is conservative and patriarchal, Korean men may have especially negative attitudes toward sexual minorities because Korean men are inclined to be more conservative.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that factors which affect homophobia were being male, religion, not having a family member or acquaintance belonging to a sexual minority group, and low self-esteem. This is consistent with the results of prior studies, which showed that males exhibit higher and more intense rates of homophobia than females [20,26,27]. As Korean society is conservative and patriarchal, Korean men may have especially negative attitudes toward sexual minorities because Korean men are inclined to be more conservative.…”
Section: Discussionsupporting
confidence: 91%
“…La asociación entre compromiso religioso y rechazo a los homosexuales podría explicarse debido a una falta de información en torno a la homosexualidad y la creencia de ideas erróneas o prejuicios que no se ajustan a la realidad, creando una imagen tergiversada de estas personas [41] . Sin embargo, se postula que la modernización está gestando un proceso de liberalización social que incluye cambios de actitudes hacia la homosexualidad [39] .…”
Section: Discussionunclassified
“…Literature on LGBT issues in Turkey is growing. Two major topics have dominated the literature so far: public attitudes towards LGBT individuals (Gelbal and Duyan, ; Oksal, ; Sakalli, ; Sakalli and Ugurlu, , ; Saraç, ) and debates on emerging gay identities (Bereket and Adam, , ; Cardoso, ; Gorkemli, ; Özbay, ; Ozyegin, ). In addition to these topics, there are individual studies on gay men in the military (Basaran, ) and strategies of LGBT individuals to manage heterosexism in everyday life (Bakacak and Öktem, ).…”
Section: Literature Reviewmentioning
confidence: 99%